A new species of Anaulacomera Stål, 1873 (Orthoptera, Tettigoniidae, Phaneropterinae) from Parque Nacional de Itatiaia, Southeastern Brazil - Antunes, André Fonseca; Takiya, Daniela Maeda (Zootaxa, 2021)
Anaulacomera currently contains 147 valid species, of those 50 are recorded from Brazil. The genus is further divided into six subgenera, which can be distinguished on characteristics of the male terminalia. A new Brazilian species is presently proposed, Anaulacomera (Anallomes) curvata sp. nov., based on three males and one female collected at Parque Nacional de Itatiaia, Itatiaia, Rio de Janeiro State. It can be distinguished from all other species because of the pair of cerciform projections of the tenth male abdominal tergite and a combination of shape and size of the male cerci.